Grønvik, Oddrun; Gundersen, Helge; Vikør, Lars; Worren, Dagfinn 2016: Norsk Ordbok. Ordbok over det norske folkemålet og det nynorske skriftmålet. - Kürschner, Sebastian (Maal og Minne, 2018)
The book under review is the twelfth and final volume of Norsk Ordbok, a dictionary of Norwegian dialectal speech and the written standard of Nynorsk. With this volume, a project spanning nearly a century comes to an end, involving several generations of dedicated and visionary researchers, having survived the troubles of seeking funding over so many years, and being both subject to and user of all the technological innovations introduced in this long time span. In this review, I will go beyond this specific final volume and take a more general perspective, including the complete work. In addition to the actual dictionary volumes, I will also consider the data resources that were developed as the empirical foundation of the dictionary and have been made publicly available.